FastLane: Agile Drop Notification for Datacenter Networks - Zats, David; Iyer, Anand; Ananthanarayanan, Ganesh; Katz, Randy; Stoica, Ion; Vahdat, Amin (2013)
The drive towards richer and more interactive web content places increasingly stringent requirements on data center networks. The speed with which such networks respond to packet drops limits their ability to meet high percentile flow completion time SLOs. Indirect notifi- cations to packet drops (e.g., duplicates in an end-to-end acknowledgment sequence) are an important limitation to the agility of response to packet drops. We propose FastLane, a new in-network drop notification mechanism. FastLane enhances switches to send high priority, per-flow drop notifications to sources, thus informing sources as quickly as possible. Consequently, sources can retransmit packets sooner and throttle transmission rates earlier. Sources can also make better decisions, given more precise information and the ability to differentiate between out-of-order delivery and packet loss. We demonstrate, through simulation and implementation, that FastLane reduces 99.9th percentile completion times of short flows by up to 75%. These benefits come at minimal cost—safeguards ensure that FastLane consume no more that 1% of bandwidth and 2.5% of buffers.